A proposed model of cognitive approach to assess clinical performance of dental students - M. Khalifah, Ayman (Journal of Stomatology, 2021)
In dental education, assessment of students is of critical value to improve their performance in clinical settings. The assessment of students’ clinical performance includes various stages, where in certain cases, assessors encounter challenges in providing final grades. This study sheds a light on assessment practices in clinical settings and focuses on assessors’ modulation of the whole cognitive process. The argument involves discussing critical thinking of assessors before, during, and after the event of assessment. Then, it analyzes a cognitive approach of assessment implied by assessors during students’ performance. Further, it proposes a model with step-by-step approach in decision-making along with different factors, which may strongly influence final grades. Four main stages were identified for the purpose of analysis, such as pre-decision, driver, primary decision, and communication stages. Each stage was supported by literary data, along with evidences worth consideration. Possible factors related to the assessment and assessors’ cognition that derived from literature were discussed in terms of the influence on the final decision towards more stringent or lenient decisions, following a temporal sequence for the proposed model events. Finally, both primary and secondary factors involved in each stage were presented.